Clever Tom and the leprechaun : an old Irish story - Shute, Linda (Scholastic Inc., 1988)
Clever Tom Fitzpatrick thinks his fortune is made when he captures a leprechaun and forces him to reveal the hiding place of his gold, but the leprechaun is clever too.